Comparison of Selenic Acid and Pyruvic Acid-Loaded Silver Nanocarriers Impact on Colorectal Cancer Viability - Özerkan, Dilşad; Kuruca, Dürdane Serap; Kariper, İshak Afşi̇n; Danişman-Kalindemirtaş, Ferdane; Erdemir, Gökçe (Springer Science and Business Media LLC, 2023)
Colorectal cancer (CRC) is a leading cause of morbidity and death worldwide. As current cancer drugs are ineffective, new solutions are being sought in other fields, including nanoscience. Similarly, silver nanoparticles play an important role in the pharmaceutical industry as they act as anti-cancer agents with less harmful effects and are usually 1 to 100 nm in size. Selenic acid (SA) and pyruvic acid (PA) are involved in various metabolic pathways in cancer. For this reason, we decided to detect their influence on colorectal cancer using silver-based (Ag) nanocarriers. DLS, Zetasizer, SEM and UV-Vis analyses were used to characterize AgSA and AgPA. A UV spectrophotometer was used to analyze the release of the NPs. MTT analyses were used to measure the viability of HCT116 and HUVEC cells, and IC50 values were calculated using GraphPad Prism. The indicated dosage and particle size of AgSA NPs proved to be suitable for cytotoxicity. Moreover, injection of these nanoparticles into non-cancer cells proved safe due to their minimal toxicity. In contrast, the AgPA NPs have no cytotoxicity and induce proliferation of HCT116 cells. Finally, only the synthesised AgSA nanoparticles could be used for advanced cancer therapy, which is both inexpensive and has minimal side effects.
Keywords: Drug Carriers; Silver; Cell Survival; Metal Nanoparticles; Antineoplastic Agents; HCT116 Cells; Pyruvic Acid; Human Umbilical Vein Endothelial Cells; Humans; Particle Size; Drug Screening Assays, Antitumor; Colorectal Neoplasms; Cell Proliferation; 3. Good health